Basic pupils´ wrong ideas about birds - Milan Kubiatko; Ivana Vaculová; Eva Pecušová (Czech Pedagogical Society, 2010)
Wrong ideas of pupils about animals have been the focus on many researchpapers. This study concentrates on investigating of basic school pupils' wrong ideas.The age of the pupils was from 10 to 16. The research tool included 30 open-endedand multiple choice questions, one question was pictorial. The total number of 719questionnaires from 7 Slovakian basic schools was included in the analyses. The itemswere divided into five categories, namely: 1. Identification of birds; 2. Reproductionof birds; 3. Food of birds; 4. Birds senses; 5. Migration of birds. The study is focusedon finding differences in results of pupils in different age groups. The large amount ofwrong ideas was found in all age groups and categories.